2021
DOI: 10.1021/acs.biochem.0c00958
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insight into the Substrate Scope of Viperin and Viperin-like Enzymes from Three Domains of Life

Abstract: Viperin is a member of the radical S-adenosylmethionine superfamily and has been shown to restrict the replication of a wide range of RNA and DNA viruses. We recently demonstrated that human viperin (HsVip) catalyzes the conversion of CTP to 3′-deoxy-3′,4′-didehydro-CTP (ddhCTP or ddh-synthase), which acts as a chain terminator for virally encoded RNA-dependent RNA polymerases from several flaviviruses. Viperin homologues also exist in non-chordate eukaryotes (e.g., Cnidaria and Mollusca), numerous fungi, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 62 publications
3
21
0
Order By: Relevance
“…The viperin-like enzyme TtVip prefers UTP as a substrate but can also utilize CTP to produce ddhCTP. 22 Therefore, we cloned, expressed, and purified TtVip and set up a reaction to produce ddhCTP as previously described by Ebrahimi et al (see Supporting Information). 17 The reaction was incubated for ∼16 h, then applied to a 10 kDa MWCO spin concentrator to separate TtVip from the reaction products.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The viperin-like enzyme TtVip prefers UTP as a substrate but can also utilize CTP to produce ddhCTP. 22 Therefore, we cloned, expressed, and purified TtVip and set up a reaction to produce ddhCTP as previously described by Ebrahimi et al (see Supporting Information). 17 The reaction was incubated for ∼16 h, then applied to a 10 kDa MWCO spin concentrator to separate TtVip from the reaction products.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Viperin (virus inhibitory protein, endoplasmic reticulum-associated, interferon-inducible) is a human antiviral protein; it is also known as RSAD2 (radical S-adenosyl methionine domain containing 2) [ 26 , [41] , [42] , [43] ]. It can act upon CTP, converting it to an analogue that blocks viral replication, but the turnover number is low (0.2 min −1 ), leading some workers to propose that its authentic substrate may be something else [ 26 , 42 , 44 , 45 ]. Viperin homologs are present in many bacteria, archaea, and fungi.…”
Section: Resultsmentioning
confidence: 99%
“…The fungal SAND has promiscuous activity and catalyses the dehydration of diverse nucleoside triphosphates (NTPs), e.g., CTP, UTP, and 5-bromo-UTP, to their ddh analogues via a mechanism requiring the transfer of an electron and a proton ( Figure 2B ) ( Ebrahimi et al, 2020b ). Next, a number of other groups characterised some microbial enzymes and showed that they catalyse dehydration of various NTPs to their ddh analogues ( Bernheim et al, 2021 ; Lachowicz et al, 2021 ) ( Figure 2C ). While the cellular function of these microbial proteins is not fully understood, the chemical reaction catalysed by SANDs can inhibit the activity of phage T7 RNA polymerase in E. coli ( Bernheim et al, 2021 ).…”
Section: Main Textmentioning
confidence: 99%